INFLUENCE OF LEADERSHIP FUNCTION, MOTIVATION AND WORK DISCIPLINE ON EMPLOYEES'PERFORMANCE - Hersona, Sonny; Sidharta, Iwan (Jurnal Aplikasi Manajemen, 2017)
This study aims to determine and analyze the influence of leadership function, motivation and work discipline on employees' performance. The population in this study is all employees at the Department of Manpower and Transmigration Karawang Regency. This research is conducted on the population of 159 people. This study uses verification research methods by using path analysis. The results show that leadership function, motivation, and work discipline have a significant effect either partially or simultaneously on employee performance. By improving the leadership function, employee motivation and work discipline, it is possible to increase the employees'performance at the Department of Manpower and Transmigration Karawang Regency.